Turkey – Russian federation relations in the new era - DERMAN, GİRAY SAYNUR (Istanbul University Press, 2021)
In this research bilateral relations between Federation of Russia and Turkey in the fields of military, economy and diplomacy are evaluated in the time period beginning from the end of the Cold War to present. In this new time period of 2000-2019, in which the era of two charismatic leaders, Vladimir Putin and Recep Tayyip Erdoğan, is taken as a basis, a balanced and effective foreign policy was followed and a series of cooperation areas were established. A new active period between the Turkey-Russia relations has started with the beginning of Vladimir Putin’s governance and both Putin and Erdoğan carried out corresponding visits and senior summit meetings were held. Though the main determinant of the bilateral relations was to enhance the security weaknesses of Turkey that appeared in the Syria issue, by developing and reinforcing the Turkish defense industry, the progress of the friendly relations between the two countries after the July 15 FETÖ coup attempt in Turkey were also examined. The shooting down of Russian warplane on November 24, 2015 was a milestone and breaking point between the two countries, however, with the normalization of relations, parties were able to reestablish political and economic cooperation in a short time. This review aims to reveal major effects of strategic partnership, security issues and energy policies of the two countries in Eurasia. After the post-Cold War era the international conjuncture was reshaped hence the Russian foreign policy decision makers changed economy, security and governmental policies to a Eurasianist approach. The consequent effects of these changes to the bilateral relations with Turkey are evaluated in this study. Relations in the context of diplomacy, economy and security of the two regional powers forms the focus point of the debate. Despite the former rivalry, the strategic relations and the vision of partnership between Turkey and Russia have developed through a win-win understanding and thus the analysis are carried out within the framework of regional cooperation in this survey. The major problems in relations and cooperation areas were also highlighted. Qualitative data analysis and induction methods were used in the analysis
Keywords: Turkey; Federation of Russia; Erdoğan; Putin; Partnership